Shadow Of A Bull - Wojciechowska, Maia (New York Aladdin Books, 1992)
Manolo olivar has to make a decision : To follow in his famous father's shadow and become a bullfighter, or to follow his heart and become a doctor
American Corner
11
Keywords: English Fiction; English Stories